Data feminism - D'Ignazio, Catherine; Klein, Lauren F. (The MIT Press, 2020)
"A new way of thinking about data science and data ethics that is informed by the ideas of intersectional feminism. Today, data science is a form of power. It has been used to expose injustice, improve health outcomes, and topple governments. But it has also been used to discriminate, police, and surveil. This potential for good, on the one hand, and harm, on the other, makes it essential to ask: Data science by whom? Data science for whom? Data science with whose interests in mind? The narratives around big data and data science are overwhelmingly white, male, and techno-heroic. In Data Feminism, Catherine D'Ignazio and Lauren Klein present a new way of thinking about data science and data ethics–one that is informed by intersectional feminist thought. Illustrating data feminism in action, D'Ignazio and Klein show how challenges to the male/female binary can help challenge other hierarchical (and empirically wrong) classification systems. They explain how, for example, an understanding of emotion can expand our ideas about effective data visualization, and how the concept of invisible labor can expose the significant human efforts required by our automated systems. And they show why the data never, ever 'speak for themselves.' Data Feminism offers strategies for data scientists seeking to learn how feminism can help them work toward justice, and for feminists who want to focus their efforts on the growing field of data science. But Data Feminism is about much more than gender. It is about power, about who has it and who doesn't, and about how those differentials of power can be challenged and changed."-
Keywords: approches et analyses; discipline; données scientifiques; histoire et politique; intersectionnalité; patriarcat; privilèges; projet charge mentale; pédagogie; racisme; rapports de pouvoir; ressource en ligne; sciences; sciences humaines; systèmes d'oppressions; thématiques; travail; travail scientifique; épistémologie

Les théories en études de genre - Lépinard, Éléonore; Lieber, Marylène (la Découverte, 2020)
Qu'est-ce que le genre ? Comment a-t-il été conceptualisé ? Est-il défini de la même façon chez les anthropologues, les sociologues, les philosophes, les historiennes et les tenantes des cultural studies ? Quelles ruptures épistémologiques ce concept a-t-il provoquées ? Cet ouvrage retrace les différentes généalogies de la notion de genre et les débats théoriques qu'elle a suscités. Il présente la variété des perspectives et des développements produits par plus de cinquante ans de recherches sur le genre et les sexualités, tant en termes de savoirs et de connaissances qu'en termes de reconnaissance et de résistance. Ce livre a pour ambition de familiariser les lectrices et les lecteurs avec les approches majeures des études de genre, dont certaines sont moins connues dans le contexte francophone. Il met également l'accent sur l'imbrication du genre avec d'autres rapports sociaux, au coeur de nombreux développements théoriques, autant hier qu'aujourd'hui
Keywords: amériques; approches et analyses; discipline; europe; genre; histoire et politique; identités LGBTQIA2+; régions géographiques; sciences humaines; sexualité; thématiques; épistémologie